The New World Belonopterygini (Neuroptera: Chrysopidae): descriptions of a new genus and species from the West Indies and comparisons among the genera - Tauber, Catherine A. (Zootaxa, 2021)
Pantaleonius toschiorum Tauber, n. gen., n.sp., is described from several islands in the Bahamas and Greater Antilles of the West Indies. For comparison, Abachrysa eureka Banks from southeastern United States is redescribed, and data on the three remaining New World belonopterygine genera, Vieira Navás, Nacarina Navás, and Belonopteryx Gerstaecker, are summarized. A key for identifying the New World belonopteryine genera is included. Although recognizably distinct, Pantaleonius shares several features with Vieira, which is considered basal within Belonopterygini. Both genera are quite different from Abachrysa Banks, which is known to be derived among the New World belonopterygines and also closely related to the Old World belonopterygine clade.